Bioengineering Beige Adipose Tissue Therapeutics - Tharp, Kevin M.; Stahl, Andreas (Frontiers in Endocrinology, 2015)
Unlocking the therapeutic potential of brown/beige adipose tissue requires technological advancements that enable the controlled expansion of this uniquely thermogenic tissue. Transplantation of brown fat in small animal model systems has confirmed the expectation that brown fat expansion could possibly provide a novel therapeutic to combat obesity and related disorders. Expansion and/or stimulation of UCP1-positive adipose tissues have repeatedly demonstrated physiologically beneficial reductions in circulating glucose and lipids. The recent discovery that brown adipose tissue-derived secreted factors positively alter whole body metabolism further expands potential benefits of brown or beige/brite adipose expansion. Unfortunately, there are no sources of transplantable brown adipose tissues for human therapeutic purposes at this time. Recent developments in bioengineering, including novel hyaluronic acid based hydrogels, have enabled non-immunogenic, functional tissue allografts that can be used to generate large quantities of UCP1-positive adipose tissue. These sophisticated tissue-engineering systems have provided the methodology to develop metabolically active brown or beige/brite adipose tissue implants with the potential to be used as a metabolic therapy. Unlike the pharmacological browning of white adipose depots, implantation of bioengineered UCP1-positive adipose tissues offers a spatially controlled therapeutic. Moving forward, new insights into the mechanisms by which extracellular cues govern stem cell differentiation and progenitor cell recruitment may enable cell-free matrix implant approaches, which generate a niche sufficient to recruit WAT derived stem cells and support their differentiation into functional beige/brite adipose tissues. This review summarizes clinically relevant discoveries in tissue-engineering and biology leading toward the recent development of beige adipose tissue implants and their potential for the metabolic therapies.